Acquired pneumonia's behavior in a community in the pediatrics service at the Fundacion Cardio Infantil, Bogotá, Colombia (2003)
Objective. To describe the population, diagnose, management and conclusion of the community acquired pneumonia (CAP) in the patients that left the pediatrics service of the Fundación Cardio Infantil (FCI in the period from January of the 2000 to December of the 2001. Materials and methods. A transversal cut study was performed with a predesigned questionnaire. 320 clinical histories were analyzed, from which 204 fulfilled the inclusion and exclusion criteria. A descriptive analysis of the variables was practiced and using a logistical regression model, the associate risk factors, complications and days of hospital habitation were identified. Results. It was proved that tachycardia was the variable which was more correlated to the presence of CAP (p=01.01);Hypoxemia, C Reactive Protein (CRP) and hemo-cultures were the principal predictors of severity (p=01.05). It was found also that the 62% of patients positively to first line antibiotics and the 54% had a hospital stay in an average of less than 5 days with not a single case of mortality. Conclusion. Advance must be done taking the clinical findings as diagnosis standards of the CAP in concordance to the suggested by the AIEPI-WHO strategy, there are other easy access variables (CRP, pulse oxymetry, cultures) as trustworthy and foretelling of gravity.